Preperation and antibacterial investigation of polycaprolactone/chitosan nano/micro fibers by using different solvent systems - Tursucular, Omer Firat; Cerkez, Idris; Orhan, Mehmet; Aykut, Yakup (Ege Universitesi mailto:teksek@mail.ege.edu.tr, 2018)
Chitosan (CHI) blended polycaprolactone (PCL) nano/micro fibers were prepared with different CHI content via electrospinning procedure. Two different solvents, acetone and formic acid (FA) were used to dissolve and blend the polymers before electrospinning process. Effect of the solvent on the electrospinability of the blend, final nano/micro fiber morphologies, chemical and thermal properties and antibacterial activities were investigated with SEM, FTIR, DSC, and ASTM 2149 01 Standard Dynamic Contact Conditions. The results revealed that chitosan particles were encapsulated in the as-spun PCL fibers with using acetone as the solvent resulted in reduced antibacterial activities Contrarily, when FA is used as the solvent, CHI and PCL were dissolved and blended very well, and enhanced antibacterial activities were obtained from as-spun PCL/CHI nano/micro fibers. © 2018 Ege Universitesi. All rights reserved.
Farkli solvent sİstemlerİ kullanilarak polİkaprolakton/kİtosan nano/mİkro lİflerİn Üretİmİ ve antİbakterİyel Özellİklerİnİn İncelenmesİ
Keywords: Antibacterial materials; Chitosan; Electrospinning; Nanofiber; Polycaprolactone